The Role of Public Speaking in Islamic Religious Education Learning in the Digital Age - Octafiona, Era; Yusnita, Erni; Kesuma, Mezan el-Khaeri (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to determine the role of public speaking in Islamic religious education learning in the digital era. The Literature Review approach was employed for the analysis. Collection of Literature Study data, typically journal articles on Google, Google Scholar, and Research Gate, is one method of resolving difficulties by searching for previously written materials. Critical appraisal was used to analyze journal data derived from the outcomes of this literature study. Critical appraisal is a journal analysis technique that serves as the rationale for the differences, similarities, and flaws. The results suggest that the role of public speaking in Islamic religious education students in the digital era is a benchmark for the creation of character education, personality, culture, courteous, spiritual, creative, and inventive. As a result, teachers are expected to be role models for students and society in general through their public speaking ability.